Model Pembelajaran Osborn Berbantuan Macromedia Flash 8 untuk Meningkatkan Kemampuan Berfikir Tingkat Tinggi (High Order Thinking Skill) Matematika - Mahgfiroh, Mahgfiroh (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2020)
The role of mathematics learning is essential as an effort to improve student thinking skills. The research aims to determine increased (high order tinhking skill) math students on the subject of cubes and beamsin the SMPN 1 Sumberjambe after usingosborn assisted learning macromedia flash 8. The kind of research used is classroom actio reaseach by the two cycle in wich one cycle consists of for steps, namely planing, action, observation and reflection. The test result of cycle 1 has been carried out by the percentage of the HOTS indicator by 27% andthe percentage of HOTS indicator by 70%. That suggests that a high level of thinking ability of the student has improved by the osborn assisted learning macromedia flash 8.